Comparison of the Efficacy of High-Dose Methylprednisolone and 6 mg Dexamethasone in Treatment in Patients with Severe COVID-19 Pneumonia - Balin, Safak Ozer; Asan, Mehmet Ali; Uysal, Serhat; Demirdag, Kutbeddin; Akbulut, Ayhan (Bilimsel Tip Yayinevi, 2023)
Introduction: The course of SARS-CoV-2 disease has a clinical spectrum ranging from mild upper respiratory tract infection to fulminant pneumonia. The use of corticosteroids is recommended in the treatment of severe COVID-19 pneumonia. The present study aimed to compare the efficacy of high-dose methylprednisolone and dexamethasone treatment in patients hospitalized with severe COVID-19 pneumonia.Materials and Methods: The participants were divided into Group M, receiving >= 250 mg intravenous methylprednisolone therapy, and Group D receiving 6 mg intravenous dexamethasone therapy. The efficacy of treatments, length of hospital stays, ventilator require-ments, anti-cytokine treatment requirements, and mortality rates were evaluated in both groups.Results: Two hundred eighty-eight (69.1%) patients received dexamethasone and 129 (30.9%) received methylprednisolone. While overall mortality in the study was 11%, this rate was 10.4% in Group D and 12.4% in Group M (p> 0.05). The rate of patients requiring intensive care was 15.8% in total, with a rate of 14.6% in Group D and 18.6% in Group M (p> 0.05). However, the total length of hospital stay was nine (7-39) days in Group M and 13 (7-29) days in Group D (p= 0.009). Anticytokines were required in 14.4% of the patients during treatment [40 in Group D, 20 in Group M (p> 0.05)].Conclusion: In this study, it was determined that early methylprednisolone treatment shortened the hospital stay. In addition, there was no statistically significant difference between Group M and Group D in terms of mechanical ventilation requirement, which showed an additional positive effect. However, mortality rates in patients receiving dexamethasone were found to be lower than in those receiving methylprednisolone, yet this difference did not reach statistical significance.
Keywords: Words; COVID-19; Steroid treatment; Mortality rate; Length of hospital stay; Ventilator requirement